The initiation codon determines the efficiency but not the site of translation initiation in Chlamydomonas chloroplasts. - Chen, X (1995)
To study translation initiation in Chlamydomonas chloroplasts, we mutated the initiation codon AUG to AUU, ACG, ACC, ACU, and UUC in the chloroplast petA gene, which encodes cytochrome f of the cytochrome b6/f complex. Cytochrome f accumulated to detectable levels in all mutant strains except the one with a UUC codon, but only the mutant with an AUU codon grew well at 24 degrees C under conditions that require photosynthesis. Because no cytochrome f was detectable in the UUC mutant and because each mutant that accumulated cytochrome f did so at a different level, we concluded that any residual translation probably initiates at the mutant codon. As a further demonstration that alternative initiation sites are not used in vivo, we introduced in-frame UAA stop codons immediately downstream or upstream or in place of the initiation codon. Stop codons at or downstream of the initiation codon prevented accumulation of cytochrome f, whereas the one immediately upstream of the initiation codon had no effect on the accumulation of cytochrome f. These results suggest that an AUG codon is not required to specify the site of translation initiation in chloroplasts but that the efficiency of translation initiation depends on the identity of the initiation codon.